Training and assistance in clean water treatment for communities to meet hygienic water needs - Bambang Suhartawan; Suyatno Suyatno; Alfred Benjamin Alfons; Andrea Karina Marielle P. Abel; Katherina T. J. Mayor Sroyer (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Yobeh Village, located in the Sentani district, consisted of 3 community units (RW) and 7 neighborhood units (RT) with a total of 173 families and 692 residents. A portion of the community, approximately 56 families with around 246 residents, lived along the shores of the island in the Lake Sentani area. The waters of Lake Sentani served as the "center of life" for the community, where the lake was utilized for fishing, disposing of household waste, and fulfilling bathing, washing, and sanitation needs. It was also used as a source of raw water for drinking and other clean water needs. This community service activity aimed to provide the community with an understanding of the importance of clean water for life. It also equipped them with the skills to assemble and operate filtration technology equipment using four filtration tubes arranged in series. Tube 1 contained bio foam media, tube 2 contained polypropylene media, tube 3 contained Granular Activated Carbon (GAC) media, and tube 4 contained Chlorine, Taste, and Odor (CTO) media. Testing the quality of the filtered water demonstrated very significant improvements, meeting the requirements for hygienic clean water suitable as raw water for drinking purposes.